Isolasi dan Karakterisasi Cendawan Dekomposer pada Bahan Kompos Jerami, Endapan Tanah Danau Tempe dan Tanah Exfarm Pertanian Universitas Hasanuddin - Fatmawati Fatmawati; Burhanuddin Rasyid; Muh. Jayadi (Universitas Hasanuddin, 2018)
Agricultural wastes able to provide profit value if utilized properly for example made into organic fertilizer. Organic fertilizer production requires microbial decomposers to help the decomposition process. This research aims to isolate and identify the characteristics of microbial decomposers found in straw compost, soil sediment from tempe lake and soil from exfarm. In this research, conducted microbial isolation. Microbial exploration of compost material, soil organic matter and soil deposition material is mixed with physiological solution then grown on PDA, further purification of the unwanted microbes. In this study only used the media to grow the asparagine fungus to see the growth of macroscopic and microscopic fungi. The results showed that there are seven isolates of the fungus from different material extraction. The extracted compost material to produce two fungi are Aspergillus sp. and Penicillium sp., Tempe lake sediment soil shows three types of fungi with Aspergillus Sp. and two types Zygomisota, while soil from Exfarm also shows two types of fungi are Aspergillus sp. and Penicillium sp. The growth rate of each different fungal isolates based sources although of the same type